KAJIAN KUAT LENTUR DAN LENDUTAN PADA VARIASI KETEBALAN PELAT BETON BUBUK REAKTIF DENGAN SILICA FUME 15% DAN PASIR KUARSA 30% - Diffa Deff Tiara Pricilia; Wibowo Wibowo; Endah Safitri (Matriks Teknik Sipil, 2024)
Abstract The need for infrastructure development is increasing in the future. The increase in the need for infrastructure development is directly proportional to the increase in concrete production. One of the concrete innovations to deal with these problems is reactive powder concrete. This concrete has advantages over conventional concrete because it can increase compressive strength, durability, and increase flexural strength. One of the applications of reactive powder concrete is concrete slab structure. This research is intended to identify the effect of concrete slab thickness dimensions on the maximum load, flexural strength, and deflection that occur in the slab. The experimental method was used with test specimens in the form of concrete slabs measuring 70 cm long, and 30 cm wide, and thickness variations of 4 cm, 5 cm, 6 cm, and 7 cm. Flexural strength testing was carried out on specimens in the form of plates and beams with dimensions of 40 cm long, 10 cm wide, and 10 cm high to determine the modulus of rupture value. The modulus of rupture test results are in the form of MOR values, then compared with the compressive strength of concrete. Flexural strength testing is done by placing the plate on top of the two pedestals with centralized loading and placing a dial gauge under the test piece to determine the amount of deflection. The test results in the form of tables and graphs show that the thickness dimension of the slab has a significant effect on the maximum load that can be received by the slab and the deflection that occurs in reactive powder concrete slabs.